PERFORMA AYAM HASIL PERSILANGAN YANG DIBERI RANSUM KADAR PROTEIN DAN DOSIS HERBAL BERBEDA - Rudy Sutrisna; M. Sofyan Sholeh (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2018)
This study aims to determine the performance of F2 resulting from crossing (Layer Stud vs. Hatcher resulting in pullet F1, F1 mated with Layer Male, resulting in F2). Performance of F2 given ration with levels of Crude Protein (CP) 16% and 18%, as well as “Herbs“. The research was carried out in a Completely Randomized Design 2 x 4 factorial pattern. Protein factors were 2 kinds of rations with Crude Protein levels of 16% and 18% of metabolic energy 3062.40 and 3013.20 kcal/kg. Herbs factor were doses of herbal dosage 0, 1, 2, 3 g/kg ration. Each treatment was repeated 4 times. Data collection performance were include rationing, giving protein, egg weight, and chicken day production, and mild shells. The results showed those the level of crude and herbal protein had no interaction, and the level of crude protein which was different was not significant (P> 0.05) on feed consumption and was significantly different (P<0.05) against crude protein consumption. Herbal treatments with doses of 1, 2 and 3 g/kg of rations did not show significant differences (P> 0.05) on feed consumption, ration crude protein, egg weight, and thick shell, but significantly different (P<0.05) from the production of hen day at without herbal treatment. Keywords: Crossbreed, Herbal Ration, Herbs, Performance, Protein Ration